Methodology, Process, and Tips for Introducing a Business Edge Program : The Case of Burkina Faso - Gomes, Mario (World Bank, Washington, DC, 2015)
One way the International Finance Corporation (IFC) strengthens the overall business environment is by making excellent training programs available to small and medium businesses. Business Edge is a perfect example. Local partner firms use these interactive learning solutions to train and mentor small business owners and their staff, resulting in more efficient businesses, higher employment, and stronger local economies. This SmartLesson shows the process methodology, including tips on how IFC implemented Business Edge in Burkina Faso, offering key lessons learned in the process.